Compliance without coercion: Effects of reporting on international labor rights. (May 2021) - Koliev, Faradj; Sommerer, Thomas; Tallberg, Jonas
While a dominant position in research on compliance holds that enforcement is necessary for states to abide by their international commitments, many international organizations (IOs) do not have recourse to such coercive means. This article offers the first systematic analysis of one prominent alternative to material coercion: compliance reporting by IOs. It develops an argument for why reporting by IOs should lead states to correct non-compliant behavior, and when those effects should be particularly strong. It tests this argument in the context of the International Labour Organization (ILO), which offers a unique setting for evaluating the impact of reporting in the absence of coercion. The principal findings are threefold. First, reporting has significant and durable effects on state respect for labor rights. Second, reporting affects compliance both immediately and when repeated over longer periods of time. Third, reporting has stronger effects on improvements in labor rights when target states are democratic and resourceful, and have a stronger presence of labor NGOs. By contrast, it does not matter to reporting's effect whether states are highly economically dependent on the outside world or whether reporting is coupled with active shaming of non-compliant states. Taken together, our results suggest that existing research has not fully appreciated the potential of monitoring systems based on reporting to generate compliance with international rules. While hard enforcement may still be important, especially in areas where incentives to renege are strong, the findings of this article suggest that it is not the exclusive path to compliance.